Lessons learned from the expansion of medical schools in Brazil: a review of challenges and opportunities - Avena, Katia M.; Quintanilha, Luiz F.; Luzardo Filho, Ricardo Luiz; Andrade, Bruno B. (Frontiers in Education, 2025)
Brazil faces significant challenges in the equitable distribution of health professionals across its vast territory, with remote and underdeveloped areas often lacking doctors. Initiatives like “Programa Mais Médicos” have expanded medical courses and residency programs nationwide. Recently, new Ministry of Education guidelines authorized courses and increased slots in response to judicial demands, highlighting the complexity of Brazil’s educational and health landscape. This initiative increased available slots, particularly in areas lacking healthcare professionals, and attracted private institutions to the medical sector. Despite advancements in expansion and geographical distribution, there are criticisms and challenges facing the current medical training process. Against this backdrop, this study offers a critical analysis of Brazil’s medical education, drawing from the experience of experts involved in the implementation of new medical schools in the Brazilian Northeast and Midwest regions. The study outlines the history, challenges, and outcomes of government policies, reflecting on future impacts and contributing to the debate on medical training quality and health service provision amidst the expansion and privatization of medical education in the country. We hope the lessons and insights can guide Brazil and other countries facing similar challenges, inspiring innovative and sustainable solutions to complex issues of doctor shortage and unequal distribution.